APPLICATION OF DIGITAL LEARNING TOOLS FOR SOLVING PRODUCTION TASKS - Vytvytska, Oksana; Tymkiv, Ivan (Physical and Mathematical Education, 2025)
Formulation of the problem. In the context of digital transformation in education and production, the ability of students to independently formulate and solve optimization problems is gaining particular importance. This requires both the application of classical mathematical methods and the use of modern digital tools. Optimization problems arise in various areas of human activity — from economics and logistics to managerial processes — making their systematic study an integral part of training professionals in different fields. Despite the availability of a wide range of established mathematical methods, the development of students’ ability to formulate an optimization problem — define the objective function, set constraints, and interpret the results in a real-world context — remains a relevant educational challenge. This ability is part of analytical and critical thinking and is a key component of the competence-based approach in education. At the same time, the effective solution of optimization problems in modern educational and professional settings is impossible without the use of digital tools such as spreadsheet processors, mathematical packages, programming environments, and web applications. These tools not only enhance motivation for learning but also significantly expand opportunities for modeling complex production or logistical processes, bringing the educational process closer to real professional activities. Materials and methods. The research uses methods of theoretical analysis, systems approach, mathematical and computer modeling, digital research tools, and result analysis. Results. Based on the analysis of a production situation, mathematical models were formulated to describe it, and solutions to the formulated optimization problems were obtained using digital educational tools. Conclusion. The approach proposed in the article to solving a production task using digital educational tools not only demonstrates the effectiveness of modern technologies in modelling real production processes but also contributes to the development of key professional competencies in learners. The use of such tools stimulates analytical thinking, fosters the ability to formulate and formalize problems, enhances digital literacy, and ensures the practical preparation of future specialists for work in a digital economy environment.